Regulatory mechanisms and applications of Lactobacillus biofilms in the food industry - Yao, Peilin; Mohd Esah, Effarizah; Zhao, Chuanping (Frontiers in Microbiology, 2025)
Lactobacillus is widely recognized for its probiotic benefits and has been widely used in food production. While biofilms are typically associated with pathogenic bacteria, they also served as a self-protective mechanism formed by microorganisms in an adverse environments. In recent years, relevant studies have revealed the excellent characteristics of Lactobacillus biofilms, offering new insights into their potential applications in the food industry. The Lactobacillus biofilms is important in improving fermentation processes and enhancing the resilience of Lactobacillus in various conditions. This paper reviews how quorum sensing regulates the formation of Lactobacillus biofilms and explores their roles in stress resistance, bacteriostasis and food production. Additionally, it highlights the emerging concept of fourth-generation probiotics, developed through biofilm technology, as a novel approach to probiotic applications.